1986
DOI: 10.1161/01.hyp.8.11.1075
|View full text |Cite
|
Sign up to set email alerts
|

Race and cardiovascular reactivity. A neglected relationship.

Abstract: SUMMARY The magnitude of the cardiovascular response to stress has been implicated in the pathogenesis of cardiovascular disease. Psychological stress procedures have received increased usage as an alternative to expensive physical (exercise) stress procedures. In the present investigation, 213 healthy, black or white, male or female children between the ages of 6 and 18 years were exposed to the psychological stress of a video game. The video game challenge was administered by a black or a white experimenter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
1

Year Published

1988
1988
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 29 publications
5
60
1
Order By: Relevance
“…20,21 Brie¯y, for the postural change stressor, the subject stood and placed the right arm at a 90 angle across the trunk and hemodynamic responses were recorded at 1 min intervals for 3 min. The 5 min video game challenge was based upon the protocol of Murphy et al 26 The subject remained supine with a 68.5 cm color television positioned at an appropriate height and angle for viewing the video game`Breakout' (Atari, Inc.). Three sets of hemodynamic readings were obtained during 1st, 3rd and 5th minute of the video game challenge, in which monetary incentive was used to increase involvement.…”
Section: Expressed As MM Hg Minmentioning
confidence: 99%
“…20,21 Brie¯y, for the postural change stressor, the subject stood and placed the right arm at a 90 angle across the trunk and hemodynamic responses were recorded at 1 min intervals for 3 min. The 5 min video game challenge was based upon the protocol of Murphy et al 26 The subject remained supine with a 68.5 cm color television positioned at an appropriate height and angle for viewing the video game`Breakout' (Atari, Inc.). Three sets of hemodynamic readings were obtained during 1st, 3rd and 5th minute of the video game challenge, in which monetary incentive was used to increase involvement.…”
Section: Expressed As MM Hg Minmentioning
confidence: 99%
“…Consistent with this hypothesis, a number of studies have demonstrated that black Americans display greater cardiovascular reactivity to a number of physical and mental stressors. For example, Murphy et al 15 reported that black children and adolescents exhibit significantly higher blood pressure increase during a video game challenge. Similarly, Dysart et al 16 and Treiber et al 17 demonstrated that black children with a family history of essential hypertension manifest greater increases in total peripheral resistance, leading to greater increases in blood pressure in response to cold pressor test and the mental stress of playing a video game.…”
Section: Pathogenesis Of Hypertension Racial Differences In Sympathetmentioning
confidence: 99%
“…[1][2][3][4] To date, stress-response studies have demonstrated that African-American (AA) men and individuals with a positive family history of hypertension have a greater propensity towards augmented BP reactivity compared with non-AA men. 4,5 These augmented BP responses appear to be mediated predominantly through changes in autonomic modulation. [5][6][7] Favourable modifications in autonomic modulation and BP have been documented following endurance training in animals and humans.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 These augmented BP responses appear to be mediated predominantly through changes in autonomic modulation. [5][6][7] Favourable modifications in autonomic modulation and BP have been documented following endurance training in animals and humans. [8][9][10][11][12] Our prior study has demonstrated an augmentation in parasympathetic or vagal modulation and enhanced baroreflex sensitivity (BRS) and arterial compliance (AC) following aerobic training.…”
Section: Introductionmentioning
confidence: 99%